ДОСЛІДЖЕННЯ ТЕПЛОФІЗИЧНИХ ХАРАКТЕРИСТИК ПАГОНІВ ВЕРБИ ЗА ДОПОМОГОЮ УСТАНОВКИ СИНХРОННОГО ТЕПЛОВОГО АНАЛІЗУ - Dmytrenko, N. V.; Ivanov, S. O.; Snezhkin, Yu. F.; Dekusha, L. V. (Institute of Engineering Thermophysics of NAS of Ukraine, 2018)
The article presents the operation principle of the device DMKI-01 and results of determination of heat capacity and specific heat of evaporation from the tree tissues of oneyear shoots of willow.